Gradation of Japanese Honorifics ‘Keigo’ as a Communication Strategy of Tourism Business Players in Bali - Andriyani, A. A. Ayu Dian; Saddhono, Kundharu; Rahayu, Ely Triasih (International Journal of Psychosocial Rehabilitation, 2020)
This research aims at describing Speech Level Marker in honorificskeigoused bytourism business playerswhile providing services to Japanese tourists. The research was conducted in BadungRegency, of which intensity of tourist visits is very high compared to other regencies in Bali. This qualitative researchemploys ethnographic approach with domain, taxonomy, componential and cultural theme analysis techniques. The research data are dialoguesbetween tourism business players consisting oftour guidesand guest relation officer staffs. The data were collected through 1) recording speeches which contain honorifics, 2) listening and taking note, and 3) nonstructured interview with 30 tourism business players. Various speeches in the form of dialogues were transcribed, translated and classified based on conversation structure and speech situation context. The research findings are:First, Gradation ofKeigoas the application of hospitality on the basis of cultural values Tri Hita Karana in giving comfort in interaction; andSecond, gradation of Japanese Keigois found when dialogue isgetting to the content of conversation in formal or informal situation in the first encounter. Therefore, it is very important for the research to be taken as a strategy in communication to improve the quality of service given toJapanese tourists in Bali.